Qualidade de vida do trabalhador de enfermagem de um hospital Estadual - Tarley, Marília Gabriela Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The search for quality of life (QOL) is now an ideal among thousands of people worldwide and is currently the subject has been studied in different areas of knowledge. Thus, one can perceive it in different dimensions, each with its due importance to people's lives. The verification of quality indexes of work life (QWL) may provide information on factors that directly interfere with the satisfaction and personal motivation and collective, with reflections on the structure and excellent service. To this end, we carried out a study to know the characacteristics of quality of life of nursing professionals in a state hospital in São Paulo State, based on short range of quality of life of the World Health Organization (WHOQOL-BREF). This work is a study with a quantitative approach, cross-sectional descriptive and exploratory data analysis using descriptive statistics, involving a sample of 281 nurses who answered the scale for measuring quality of life, composed of four areas: physical, psychological, social relationships and environment. In the study, these areas were related to the professional position, and shift work. There was a satisfactory quality of life in the study population in different areas of WHOQOL-BREF. There was no statistically significant changes in quality of life among the variables. It follows that the population presented data consistent with an adequate quality of life, thus making relevant to addressing the quality of life of nursing in a healthcare organization which has as fundamental to the pursuit of quality through the accreditation process second hospital established by the National Accreditation Organization (ONA) that aims at establishing and implementing a process of improving health care, thereby stimulating the services to achieve higher standards of quality

A busca pela qualidade de vida (QV) é hoje um ideal entre milhares de pessoas do mundo inteiro e atualmente este tema tem sido estudado em diferentes áreas do conhecimento. Assim, pode-se percebê-la sob diversas dimensões, cada uma com sua devida importância para a vida das pessoas. A verificação de índices de qualidade de vida no trabalho (QVT) pode trazer informações de fatores que interferem diretamente na satisfação e motivação pessoal e coletiva, com reflexos na excelência da estrutura e do serviço. Para tanto, realizou-se um estudo com o objetivo de conhecer as características da qualidade de vida dos profissionais de enfermagem de um hospital estadual do interior paulista, tendo como base a escala abreviada de qualidade de vida da Organização Mundial de Saúde (WHOQOL-BREF). O presente trabalho consiste de um estudo com abordagem quantitativa, transversal, exploratório-descritivo com análise dos dados por meio da estatística, envolvendo uma amostra de 281 profissionais de enfermagem que responderam a escala de aferição da qualidade de vida, composta por quatro domínios: físico, psíquico, relações sociais e meio- ambiente. No estudo, esses domínios foram relacionados com o cargo profissional, turno e local de trabalho. Observou-se uma qualidade de vida satisfatória na população estudada, nos diversos domínios da escala WHOQOL-BREF. Não houve alterações estatisticamente significativas da qualidade de vida entre as variáveis estudadas. Conclui-se que a população estudada apresenta dados compatíveis com uma qualidade de vida adequada, tornando então relevante à abordagem da qualidade de vida dos trabalhadores de enfermagem em uma organização de saúde que tem como aspecto fundamental a busca da qualidade por meio do processo de acreditação hospitalar segundo estabelecido pela Organização Nacional de Acreditação (ONA) que tem... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Enfermagem; Qualidade de vida no trabalho